A chromosome-level genome assembly of the cabbage aphid Brevicoryne brassicae - Jun Wu; Guomeng Li; Zhimou Lin; Yangzhi Zhang; Wenyuan Yu; Rong Hu; Shuai Zhan; Yazhou Chen (Scientific Data)
Abstract The cabbage aphid, Brevicoryne brassicae, is a major pest on Brassicaceae plants, causing significant yield losses annually. However, the lack of genomic resources has hindered progress in understanding this pest at the molecular level. Here, we present a high-quality, chromosomal-level genome assembly for B. brassicae, based on PacBio HiFi long-read sequencing and Hi-C data. The final assembled genome size was 429.99 Mb, with a scaffold N50 of 93.31 Mb. Notably, 96.19% of the assembled sequences were anchored to eight chromosomes. The genome covered 99.24% of BUSCO genes and 95.16% of CEGMA genes, indicating a high level of completeness. By integrating high-coverage transcriptome data, we annotated 22,671 protein-coding genes and 3,594 lncRNA genes. Preliminary comparative genomic analyses focused on genes related to host colonization, such as chemosensory- and detoxification-related genes, as well as cross-kingdom lncRNA Ya. In summary, this study presents a contiguous and complete genome for B. brassicae, which will advance our understanding of the molecular mechanisms underlying its host adaptation, pest behavior, and interaction with Brassicaceae plants.